Investigation of the influence of crop cultivation technologies on soil compaction in the steppe zone of Ukraine - Kobets, Anatoly Stepanovich; Kobets, Anatoly S.; Kobets, Anatoly; Kobec, A. S.; Сobets’, Anatoliy S.; Кобець, Анатолій Степанович; Derkach, Oleksii; Деркач, Олексій Дмитрович; Volovyk, Iryna; Воловик, Ірина Анатоліївна; Nor, Kyrylo; Нор, Кирило (SCIENTIFIC TECHNICAL UNION OF MECHANICAL ENGINEERING “INDUSTRY 4.0”, 2023)
The article presents the results of the action of agricultural machinery on soil compaction - chernozems. The dependence of changes in soil compaction on crop cultivation technologies is shown. A comparison is made for such technologies as No-Tillage and traditional. The technique used in these technologies is analyzed. Conclusions were made and recommendations were given to reduce the negative impact of technology on the soil. У статті наведено результати дії сільськогосподарської техніки на ущільнення ґрунту – чорнозему. Показано залежність зміни ущільнення ґрунту від технологій вирощування сільськогосподарських культур. Проводиться порівняння таких технологій, як No-Tillage і традиційна. Проаналізовано техніку, яка використовується в цих технологіях. Зроблено висновки та надано рекомендації щодо зменшення негативного впливу техніки на ґрунт.
Дослідження впливу технологій вирощування сільськогосподарських культур на ущільнення ґрунту у степовій зоні України
Keywords: growing technology; технологія вирощування; soil compaction; ущільнення грунту; soil deformation energy; енергія деформації грунту